DANCE TO WELLNESS: THE GOBHANGRA WORKOUT'S HEALTH IMPACT ACROSS DIVERSE POPULATIONS : DANCE TO WELLNESS - Singh, Jasveen Kaur Grewachan; Nambiar, Nisha (STIKes Mandala Waluya Kendari, 2025)
Background: The GoBhangra Workout is a culturally adaptive fitness class that utilizes traditional Punjabi Bhangra and Bollywood dance fused with specialized adaptations for various types of abilities that leads to exceptional health and wellness benefits for people of all abilities. This research specifically looks at programs around inclusive fitness and highlights benefits, difficulties in participation, as well as the role of cultural factors like the GoBhangra Workout in issues of physical and mental health. Methods: This research uses a mixed-methods approach to examine the impacts, challenges, and facilitators of inclusive fitness programming through a systematic literature review and in-depth qualitative case study analysis. A systematic review in relation to the IEPs published from 2015 to 2024 was conducted to identify trends and assess overall health benefits associated with the programs. Results: Thematic analysis was conducted with the qualitative data in relation to finding important themes surrounding the physical and psychological health related implications, as well as social and cultural benefits, of inclusive fitness. Qualitative study focused on a case study approach utilizing 15 semi- structured interviews. In the quantitative methodologies there were all major outcomes of physical and mental health associated with participation in exercise programs. Conclusion: The results of this study generate evidence-based recommendations for the expansion of these programs.